PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PBM) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV PADA TEMA 1 SDN 158 PEKANBARU - Maimanah Hasan; Neni Hermita (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
The implementation of the Problem-Based Learning model encourages students to be active in the teaching and learning process, actively think, and develop problem-solving skills, thereby creating active and independent learning that can improve student learning outcomes. To strengthen the scientific approach, it is recommended to apply Problem-Based Learning to encourage students to be creative and contextual, both individually and in groups. The purpose of this study was to improve the learning outcomes of Grade IV students on Theme I at SDN 158 Pekanbaru by applying the Problem-Based Learning model. This type of research was classroom action research with a collaborative pattern. The purpose of this classroom action research was to improve student learning outcomes and enhance the quality of learning practices applied. The research subjects were Grade IVA students at SDN 158 Pekanbaru, totaling 31 students, consisting of 13 female and 18 male students. The data collection instruments used in this study were observation sheets of teacher and student activities, observation sheets of student attitudes, and learning outcome tests. The data analysis technique used in this study was descriptive quantitative analysis. The results of this study showed that the application of the Problem-Based Learning model could improve student learning outcomes in Sub-theme 2 and Sub-theme 3, namely the baseline score (UH Sub-theme 1), which averaged 69.03, increased in Cycle I daily test (UH Sub-theme 2) to an average of 73.70, and further increased in Cycle II daily test (UH Sub-theme 3) to 84.03. Teacher and student activities at each meeting in Cycle I and Cycle II experienced an increase, although there were occasional fluctuations.